The printed cyrilic primers of the first half of XVII century are in Belarus: a historicol and pedagogical analysis (to the 500th anniversary of the Belarusian typography) - Ershova, Olga I. (Journal of the Belarusian State University. Journalism, 2019)
The printed cyrillic primers of the first half of the XVII century published on Belarussian earth are examined in the context of sociocultural processes in Great Duchy Lithuanian. The structure and content of the primer as a training book is analyzed. The features of the Belarussian primers are examined. The primers of S. Sobolya of 1631 is described in detail. The value of primers opens up for education of students in a spirit orthodox religion. Meaningfulness of primers is shown from the point of view of forming of sociality of man XVII century.